Association of Depressive Symptoms with Sleep Disturbance: A Co-twin Control Study. Issue 3 (15th May 2021) - Huang, Minxuan; Bliwise, Donald L; Hall, Martica H; Johnson, Dayna A; Sloan, Richard P; Shah, Amit; Goldberg, Jack; Ko, Yi-An; Murrah, Nancy; Levantsevych, Oleksiy M; Shallenberger, Lucy; Abdulbagki, Rami; et al.
Abstract: Background: Few studies have comprehensively evaluated the association of depression with sleep disturbance using a controlled twin study design. Purpose: To cross-sectionally evaluate the association of depression with both objective and subjective sleep disturbance. Methods: We studied 246 members of the Vietnam Era Twin Registry. We measured depressive symptoms using the Beck Depression Inventory-II (BDI) and assessed major depression using structured clinical interviews. Twins underwent one-night polysomnography and 7-day actigraphy to derive measures of objective sleep and completed the Pittsburgh Sleep Quality Index for subjective sleep. Multivariable mixed-effects models were used to examine the association. Results: Twins were all male, mostly white (97%), with a mean (SD) age of 68 (2). The mean (SD) BDI was 5.9 (6.3), and 49 (20%) met the criteria for major depression. For polysomnography, each 5-unit higher BDI, within-pair, was significantly associated with 19.7 min longer rapid eye movement (REM) sleep latency, and 1.1% shorter REM sleep after multivariable adjustment. BDI was not associated with sleep architecture or sleep-disordered breathing. For actigraphy, a higher BDI, within-pair, was significantly associated with lower sleep efficiency, more fragmentation and higher variability in sleep duration. BDI was associated with almost all dimensions of self-reported sleep disturbance. Results did not differ by zygosity, and remained consistent using major depression instead of BDI and were independent of the presence of comorbid posttraumatic stress disorder and antidepressant use. Conclusions: Depression is associated with REM sleep disruption in lab and sleep fragmentation and sleep variability at home, but not with sleep architecture or sleep-disordered breathing. Abstract : Depression is associated with rapid eye movement sleep disruption, sleep fragmentation and variability, but not with sleep architecture or sleep-disordered breathing